2018
DOI: 10.1039/c8ob02644k
|View full text |Cite
|
Sign up to set email alerts
|

An effective and facile synthesis of new blue fluorophores on the basis of an 8-azapurine core

Abstract: A new efficient route for the synthesis of blue fluorescent triazolopyrimidines for biological applications is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Absolute quantum yield study was performed on Horiba FlouroMax 4 Spectrofluorometer (Kyoto, Japan) with Quanta-φ integrating sphere using FluorEssence 3.5 Software. DTPs 1a-e, 2a-c and 3a-b were prepared according to procedures reported in the literature and their spectral characteristics were identical to the published data [8,21]. were prepared via the demethylation of their methoxycongeners by using BBr 3 solution in dichloromethane with special temperature profile regime (Scheme 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Absolute quantum yield study was performed on Horiba FlouroMax 4 Spectrofluorometer (Kyoto, Japan) with Quanta-φ integrating sphere using FluorEssence 3.5 Software. DTPs 1a-e, 2a-c and 3a-b were prepared according to procedures reported in the literature and their spectral characteristics were identical to the published data [8,21]. were prepared via the demethylation of their methoxycongeners by using BBr 3 solution in dichloromethane with special temperature profile regime (Scheme 1).…”
Section: Methodsmentioning
confidence: 99%
“…Recently we reported the synthesis and photophysical properties of new blue and blue-green fluorophores derived on dihydro-1,2,3-triazolopyrimidine core (DTP) [8]. These fluorophores exhibited multifunctional properties and showed good fluorescence in solutions (with QY up to 88%, Stokes shift (SS) ~151 nm and λ em up to 534 nm).…”
Section: Introductionmentioning
confidence: 99%
“…Among the wide variety of azolopyrimidines, special attention should be paid to the isomorphic analogues of naturally occurring purines, 8-azapurines, with useful biological activity , and high photophysical properties. , The structural features of 8-azapurines allow for their substitution of natural purine bases in numerous enzymatic processes, as well as their application as fluorescent probes in enzymology …”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that this method was successfully used for the synthesis of a 2-aryl-1,2,3-triazole ring II (Scheme a) . Another example is construction of 8-azapurine derivatives IV with significant photophysical properties , (Scheme b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation